The bioethical aspects of the new eugenics - Renata Luchini Paes da Silva; Joseval Martins Viana (Universidade de Sao Paulo, 2020)
With the advances in biotechnology and in the Human Genome Mapping Project, the ability to manipulate the DNA and perform gene therapy has increased and raised some concerns. The new eugenic theory is one of them. The concept of eugenics first appeared in the late nineteenth century1, as a theory of the improvement of the human race. It nearly disappeared after World War II2 but is now returning with new theories and ethical debates. The purpose of this study is to present some considerations regarding contemporary and widespread technological advances in assisted reproduction. We bring attention to the relations between assisted reproduction and a possible new eugenic policy, stressing the relevance of the matter and discussing some of the implied ethical issues. We do not intend to conduct a comprehensive study on the subject, but to provide some considerations that may contribute to further debate. A literature review was conducted focused on the ethical, bioethical and legal aspects of eugenics. In addition, some media coverage on the current use of the above-mentioned technologies was also consulted.